Shared decision making, satisfaction with care and medication adherence among patients with diabetes. Issue 3 (March 2020) - Milky, Gediwon; Thomas, Joseph
Highlights: Older age, being male and, no insurance were associated with low SDM. Patients with lower perceived health had low involvement in SDM. SDM was associated with higher satisfaction with care. Abstract: Objectives: We examined factors associated with shared decision making and whether shared decision-making (SDM) was associated with satisfaction with care or with adherence to anti-diabetic medication. Methods: A retrospective study was conducted using 2011–2014 Medical Expenditure Panel Survey (MEPS) data. Inclusion criteria were 18 years or older and visit to a usual source of care during the prior 12 months. Exclusion criteria were reported cognitive limitation, proxy response, less than two prescription fills, or missing data on study variables. SDM was assessed using seven MEPS items. Satisfaction with care was assessed using a single MEPS item 12 months after SDM measurement. Adherence was assessed using Medication Possession Ratio in 12 months after SDM measurement. Results: The weighted sample of 797 respondents represented 15.6 million with diabetes. Being older, male, or uninsured were associated with low SDM. High SDM was associated with higher satisfaction (p < 0.0001). SDM was not associated with adherence. Conclusions: Patients with higher SDM were more satisfied with their healthcare. We did not find association between SDM and adherence to antidiabetic medication. Practice implications: Involvement in SDM is encouraged to improve patient satisfaction. Providers may consider age, sex and insurance status in facilitating communications to improve SDM.